Sentential Context Modulates the Involvement of the Motor Cortex in Action Language Processing: An fMRI Study - Schuil, Karen D.; Smits, Marion; Zwaan, Rolf A. (Frontiers in Human Neuroscience, 2013)
Theories of embodied cognition propose that language comprehension is based on perceptual and motor processes. More specifically, it is hypothesized that neurons processing verbs describing bodily actions, and those that process the corresponding physical actions, fire simultaneously during action verb learning. Thus the concept and motor activation become strongly linked. According to this view, the language-induced activation of the neural substrates for action is automatic. By contrast, a moderate view of embodied cognition proposes that activation of these motor regions is modulated by context. In recent studies it was found that action verbs in literal sentences activate the motor system, while mixed results were observed for action verbs in nonliteral sentences. Thus, whether the recruitment of motor regions is automatic or context dependent remains a question. We investigated functional magnetic resonance imaging activation in response to nonliteral and literal sentences including arm and leg related actions. The sentence structure was such that the action verb was the last word in the subordinate clause. Thus, the constraining context was presented well before the verb. Region of interest analyses showed that action verbs in literal context engage the motor regions to a greater extent than nonliteral action verbs. There was no evidence for a semantic somatotopic organization of the motor cortex. Taken together, these results indicate that during comprehension, the degree to which motor regions are recruited is context dependent, supporting the weak view of embodied cognition.